Thrombocytopenia after Implantation of the Perceval, Intuity, and Sapien Aortic Valve Prostheses - Haeussler, Achim; Ntinopoulos, Vasileios; Rings, Laura; Papadopoulos, Nestoras; Hoti, Gojart; Fleckenstein, Philine; Dzemali, Omer (The Thoracic and Cardiovascular Surgeon, 2022)
Background An increased incidence of thrombocytopenia was reported after implantation of the LivaNova Perceval and the Edwards Sapien aortic valve bioprostheses. Aim of this study is to assess the perioperative platelet count and bleeding complications in three different types of aortic valve bioprostheses intended for high-risk patients, the sutureless LivaNova Perceval, the rapid deployment Edwards Intuity, and the transcatheter Edwards Sapien.Methods We performed a retrospective analysis of the perioperative data of patients receiving the Perceval, Intuity, and Sapien aortic valve bioprosthesis. The platelet count was collected preoperatively, at nadir postoperatively, and at discharge. The bioprostheses were compared for between-group differences in platelet count and postoperative bleeding complications.Results Overall, 37 patients received the Perceval, 42 the Intuity, and 58 the Sapien bioprosthesis. There was no significant between-group difference in the preoperative platelet count [Perceval 203(178–246)G/l, Intuity 214(190–232)G/l, Sapien 201(178–275)G/l, p = 0.800]. There was a significant between-group difference in the postoperative platelet count, both at nadir value [Perceval 57(37–80)G/l, Intuity 91(73–109)G/l, Sapien 126(105–170)G/l, p < 0.0001] and at discharge [Perceval 150(83–257)G/l, Intuity 239(200–343)G/l, Sapien 232(179–284)G/l, p = 0.001]. There was no significant between-group difference regarding red blood cell transfusions (p = 0.242), platelet transfusions (p = 0.656), and rethoracotomy for bleeding (p = 0.847).Conclusion We found a significant platelet count reduction in all three bioprostheses which was more marked in the Perceval group. The platelet count reduction was transient and fully recovered in the Intuity and Sapien groups, whereas the Perceval group showed only a partial platelet count recovery. However, bleeding complications were not different between the three bioprostheses.
Keywords: aortic valve bioprosthesis; transapical TAVI; outcomes (includes mortality and morbidity)